The Roussillon Basin (S. France): A case-study to distinguish local and regional events between 6 and 3 Ma. (September 2015) - Clauzon, Georges; Le Strat, Paul; Duvail, Cédric; Do Couto, Damien; Suc, Jean-Pierre; Molliex, Stéphane; Bache, François; Besson, David; Lindsay, Everett H.; Opdyke, Neil D.; Rubino, Jean-Loup; Popescu, Speranta-Maria; et al.
Abstract: The Roussillon Basin is a non-silled Miocene sedimentary basin filling a late Oligocene–early Miocene graben. The basin was intensively impacted by the Messinian fluvial erosion, as evidenced in exposed sections, in seismic profiles and in deep boreholes drilled for hydrocarbon exploration. As the basin was open to the Mediterranean Sea, the huge drop in sea level at the peak of the Messinian Salinity Crisis is clearly recorded, along with the subsequent sudden marine reflooding and the resulting prograding sedimentary filling, particularly in Gilbert-type fan deltas. Here, the Messinian Erosional Surface (MES) is accurately mapped in a high-resolution document, which corrects the confusion resulting from the set of 1:50, 000 scale regional maps. Aim of the 3D reconstruction of the MES is to modernize geological mapping, a crucial challenge for Mediterranean and peripheral areas. Thanks to a reliable chronostratigraphy provided by planktonic foraminifers, calcareous nannofossils, micro- and macro-mammal remains, paleomagnetism and a 10 Be cosmogenic nuclide-derived study, our reconstruction is one of the most comprehensive models of changes in sea level from 6 to 3 Ma. After the marine reflooding of the Mediterranean Basin at 5.46 Ma, the fluctuations in sea level recorded in the Roussillon Basin were forced by global changes. Following reflooding, the Prades large olistostrome collapsed prepared by the previous exhumation along the Canigou fault. The olistostrome is a good example of a local accident resulting from Messinian events. The exceptional changes in sea level at the peak of the Messinian Salinity Crisis deeply marked the Roussillon Basin, momentarily overprinting the Pyrenean orogenesis. Highlights: The Messinian Salinity Crisis severely impacted the Roussillon area. Maps of the Messinian Erosional Surface clarify the regional geological context. The sudden post-crisis marine reflooding induced proximal Gilbert-type fan deltas. Sea level controlled lateral-vertical variations in sedimentation. The Prades olistostrome resulted from isostatic rebounds due to the Messinian Crisis.